2008
DOI: 10.1088/0953-8984/20/10/104262
|View full text |Cite
|
Sign up to set email alerts
|

Flux dependence of cluster formation in neutron-irradiated weld material

Abstract: The effect of neutron flux on the formation of irradiation-induced clusters in reactor pressure vessel (RPV) steels is an unresolved issue. Small-angle neutron scattering was measured for a neutron-irradiated RPV weld material containing 0.22 wt% impurity Cu. The experiment was focused on the influence of neutron flux on the formation of irradiation-induced clusters at fixed fluence. The aim was to separate and tentatively interpret the effect of flux on the characteristics of the cluster size distribution. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Refs. [36,37]). Under steady-state conditions, the concentration of the vacancies can be estimated by [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [36,37]). Under steady-state conditions, the concentration of the vacancies can be estimated by [37].…”
Section: Resultsmentioning
confidence: 99%
“…Note the strong variation of C vac with temperature, dislocation density and dose rate. The stationary concentration of self-interstitials [37].…”
Section: Resultsmentioning
confidence: 99%
“…Small angle neutron scattering (SANS) is another powerful probe to characterize nanoscale structures [12,13,[16][17][18][19]. For 14YWT, Alinger et al [13] reported a particle size of 2-3 nm, but it is clear from the SANS intensity data [12] that more than one particle size exists.…”
Section: Introductionmentioning
confidence: 99%
“…Flux (dose rate) effects on the microstructure of neutron-irradiated RPV steels and model alloys are an important issue [20][21][22]. In the work reported here, a relatively high specific value of flux was applied intentionally and flux effects are not considered.…”
Section: Introductionmentioning
confidence: 99%